Pengaruh Substitusi Tempe, Penambahan Puree Wortel dan Puree Daun Kelor terhadap Kandungan Protein, Serat Pangan, Zat Besi, dan Bioassesibilitas Zat Besi Sosis Sapi: Effect of Tempeh Substitution, Addition of Carrot Puree and Moringa Leaf Puree on Protein, Fiber, Iron Content, and Iron Bioaccessibility of Beef Sausage - Azizi, Elsa Carla; Rimbawan, Rimbawan; Marliyati, Sri Anna (Amerta Nutrition, 2025)
Background: Cases of iron deficiency anemia among adolescent girls in Indonesia remain high. To address this issue, there is a need to formulate an inexpensive sausage product with relatively high protein, iron, and fiber content. Objectives: This research was conducted to analyze the effect of tempeh substitution, carrot puree addition, and moringa leaf puree addition on the protein content, dietary fiber, iron, and Fe bioaccessibility in beef sausages. Methods: This study employed a true experimental design to develop sausage formulations and analyze their protein content, dietary fiber, iron content, and iron bioaccessibility. A 3-factor factorial design was used, with factors including tempeh substitution, carrot puree addition, and moringa leaf puree addition. Results: The protein content in the sausages was not influenced by any individual factor or interaction between factors, with values ranging from 6.27% to 6.91%. Fiber content was only affected by tempeh substitution, ranging from 11.89 to 13.84 mg/100 g. Iron bioaccessibility was influenced by both tempeh substitution and moringa leaf puree addition, with bioaccessibility values ranging from 84.3% to 87.1%. The highest bioaccessibility was observed with 40% tempeh substitution, 20% carrot puree addition, and 6% moringa leaf puree addition. Conclusions: Tempeh substitution significantly affected fiber content, iron content, and iron bioaccessibility. Carrot puree addition had no effect on any parameter, while moringa leaf puree addition influenced only iron bioaccessibility.